Consortium of Microorganism and Their Effects on Peanut Pod Yield - Bolonhezi, Denizart (2020)
The objective of this study was to evaluate yield and pod maturity condition in peanut lines of the runner type, so as to indicate cultivars with reduced cycle. Maturity assesment was evaluated in two sampling dates before harvesting. The experiment was carried out in Ribeirão Preto, SP, Brasil, in randomized blocks design, testing tem breeding lines and two control cultivars. Pod maturity was evaluated at 119 and 125 days after planting. In each sampling date the plants contained in 0,5m of row were collected and pod maturity was determined based in a maturity table considering the color of the pod mesocarp, in a scale varying from white to black. Harvesting to evaluate yield was done at 125 days after planting, by digging one of the two lines of each plot. Along with pod yield, the following variables were obtained: percentage of the number of mature pods in each sampling date and the percentage of increase in mature pods from the 119 to 125 sampling dates. The results indicated that, when harvesting at 125 days, the line 13.24 as the most productive (7,625 kg ha-1). At 119 days after planting, the line 13.34 showed the highest percentage of mature pods (56.1%). The lines 13.15 and 13.24 showed the largest increases in number of mature pods from the 119th to the 125th day after planting. The results indicate that there are promising lines for selection as new cultivars combining productivity and earliness, to be confirmed in other environments.